1990
DOI: 10.1021/bi00465a018
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of Escherichia coli dihydrofolate reductase: the NADP+ holoenzyme and the folate .cntdot. NADP+ ternary complex. substrate binding and a model for the transition state

Abstract: The crystal structure of dihydrofolate reductase (EC 1.5.1.3) from Escherichia coli has been solved as the binary complex with NADP+ (the holoenzyme) and as the ternary complex with NADP+ and folate. The Bragg law resolutions of the structures are 2.4 and 2.5 A, respectively. The new crystal forms are nonisomorphous with each other and with the methotrexate binary complex reported earlier [Bolin, J. T., Filman, D. J., Matthews, D. A., Hamlin, R. C., & Kraut, J. (1982) J. Biol. Chem. 257, 13650-13662]. In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
356
0
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(375 citation statements)
references
References 39 publications
18
356
0
1
Order By: Relevance
“…This is in contrast to the adenosine moiety for both NADPH and NADP', where shifts in their respective Raman spectra clearly show the result of protein interactions. These data are in general agreement with X-ray results (Bystroff et al, 1990) which show the oxidized nicotinamide ring in binary complex with DHFR to be disordered, suggesting that the group may reside in solution, while the electron density patterns for the rest of the cofactor are well defined and place the adenosine moiety in its protein binding pocket. This may be a result from there being no compensating polar groups at the nicotinamide binding pocket which could stabilize the charge on the positive NADP' (Bystroff et al, 1990).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This is in contrast to the adenosine moiety for both NADPH and NADP', where shifts in their respective Raman spectra clearly show the result of protein interactions. These data are in general agreement with X-ray results (Bystroff et al, 1990) which show the oxidized nicotinamide ring in binary complex with DHFR to be disordered, suggesting that the group may reside in solution, while the electron density patterns for the rest of the cofactor are well defined and place the adenosine moiety in its protein binding pocket. This may be a result from there being no compensating polar groups at the nicotinamide binding pocket which could stabilize the charge on the positive NADP' (Bystroff et al, 1990).…”
Section: Resultssupporting
confidence: 88%
“…DHFR from E. coli was prepared as previously described (Bystroff et al, 1990) and stored at 4°C in 10 mM TridHCl, pH 8.0, 1 mg/ml 0.5 M KCI. Before use, insoluble protein was removed by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…NAD(P) binding to dehydrogenases has been studied in detail [ 11,121. It was shown that upon binding of the coenzyme, alcohol dehydrogenases undergo a large conformational change: the catalytic domain makes a large rigid-body rotation towards the coenz~e-binding domain. Similar studies have been performed for NADP+ in dihydrofolate reductase [13], the thiamin diphosphate dependent enzyme transketolase 1141, and other enzymes [15].…”
Section: Introductionsupporting
confidence: 61%
“…First, residues from regions which have ill-defined electron density (residues 19,137,200,330). Second, residues from intersubunit contact areas (residues 13,19,87). Third, residues from flexible loops near the flavin binding site.…”
Section: Structure Of Apo-enzymementioning
confidence: 99%
“…The apo enzyme is difficult to crystallize (Bystroff & Kraut, 1991), so we chose to examine the binary complex with the inhibitor methotrexate. Methotrexate binds in the folate-binding site and leaves the NADP site empty Filman et al, 1982;Bystroff et al, 1990;Bystroff & Kraut, 1991). To create the binary complex, 20 mg of apo enzyme was dialyzed against 0.1 M Tris buffer (pH 7.0).…”
Section: Methodsmentioning
confidence: 99%